A unique "solidified" human brain from Asunción (XX century CE, Paraguay). (February 2023) - D'Anastasio, R.; Arrizza, L.; Cilli, J.; Capasso, L.
Highlights: María Guggiari Echeverría (1925–1959) is the most venerated Blessed in Paraguay. Her relics consist of the naturally preserved body, including the brain. The brain is small, hard, brittle, mainly composed of carbon. The cerebral hemispheres and the cerebellum show anatomical and histological features. The brain underwent a process of carbonization, never observed in other cases. Abstract: A relic (from the Latin reliquiae : remains) is the body (or part) of a deceased holy person or belongings kept as an object of reverence. The long-term preservation of relics is a priority for many religious and secular communities and often anthropologists, involved in their restoration for conservative purposes, collect anthropological and paleopathological data of scientific interest. In this context, the Authors present the case of Blessed Maria Felicia Guggiari Echeverria (1925–1959), the most revered Catholic figure in Paraguay, whose remains consist of a complete and well preserved skeleton, fragments of adipocere, and complete " solidified " brain and cerebellum. The brain and the cerebellum have a reduced volume of about 85 cm 3, and a hard and friable consistency. Microscopic analyses have shown the presence of still distinguishable histological structures (e.g. the stratification of the cerebral cortex, meninges, residual vessels, and probable nerve bundles). Microanalysis showed the presence of uniformly distributed carbon (C), oxygen (O) and other chemical elements (e.g. Na, Ca, Mg, K) variably distributed. The FTIR analysis highlighted the presence of proteins. The brain probably underwent a process of carbonization, which involves a reduction in volume due to loss of O and H and the consequent concentration of C in low-oxygen conditions. The presence of adipocere, which is formed in environmental conditions similar to those of carbonization, supports this hypothesis. The "solidified" brain of Blessed Maria Felicia Guggiari Echeverria (1925–1959) represents today a unique case.